2015
DOI: 10.1159/000442265
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a de novo Supernumerary Neocentric Ring Chromosome Derived from Chromosome 7

Abstract: Supernumerary ring chromosomes (SRC) are usually derived from regions adjacent to the centromere. Their identification may be challenging, particularly in case of low mosaicism. Here, we report on a patient who was referred for major in utero growth retardation, severe developmental delay, facial dysmorphism, cleft palate, and hypospadias. The karyotype showed a small SRC in mosaic. The combination of FISH, M-FISH and array-CGH was necessary for a complete characterization of this SRC. M-FISH revealed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Recently, Kumar et al reported a child with dysmorphic features and developmental delay, who presented a complex chromosome rearrangement involving chromosome 7 and resulting of a class II/McClintock mechanism [6]. Louvrier et al [7] reported a mosaic neocentric ring involving the region 7q22.1q31.1, in a child with a severe global retardation and dysmorphic features. In this case, the aSMC characterization, using arrayCGH, and the clinical description are very detailed establishing a clear genotype-phenotype correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kumar et al reported a child with dysmorphic features and developmental delay, who presented a complex chromosome rearrangement involving chromosome 7 and resulting of a class II/McClintock mechanism [6]. Louvrier et al [7] reported a mosaic neocentric ring involving the region 7q22.1q31.1, in a child with a severe global retardation and dysmorphic features. In this case, the aSMC characterization, using arrayCGH, and the clinical description are very detailed establishing a clear genotype-phenotype correlation.…”
Section: Introductionmentioning
confidence: 99%